Pharmacy hydroxyurea education materials for patients with sickle cell disease: An environmental scan and assessment of accuracy. Issue 5 (21st January 2020) - Cervi, Andrea; Diamantouros, Artemis; Azzam, Mona; Lane, Shannon J.; Sapru, Hyra; Verhovsek, Madeleine
Abstract: Background: Hydroxyurea (HU) remains a cornerstone of sickle cell disease (SCD) therapy; however, its use is limited by poor patient adherence owing to concerns about side effects. Pharmacies routinely provide patients with handouts about HU, which, we hypothesized, contain inaccuracies that may contribute to negative patient perceptions of HU. Methods: We used a systematic approach to collect and review patient information handouts (PIHs) on HU from pharmacies in Ontario, Canada. PIHs were evaluated according to: i. Number of inaccurate statements, ii. Percentage of essential statements based on comparison with a reference standard PIH developed by the Canadian Haemoglobinopathy Association (CanHaem), and iii. Reading level. Results: PIHs were collected from 98% of chain and community pharmacies registered in Ontario. All PIHs contained inaccurate statements, most frequently relating to the risk of developing cancer. Only 33% of PIHs identified SCD as an indication for HU use. Pharmacy PIHs contained 45% of the essential statements present within the CanHaem HU PIH, neglecting to mention use of HU for management of SCD and benefits of HU in preventing SCD complications. Moreover, the reading level across pharmacy PIHs was 1.8 grades higher than that advised for written patient education materials. Conclusion: Patients who are prescribed HU are likely to be provided with PIHs that contain inaccuracies that are weighted toward the risks of HU therapy and run contrary to published literature. This study identifies a gap in the care of patients with SCD and an opportunity to improve the quality of HU PIHs to help patients make well‐informed decisions about their health.